Research Challenges for Visualization Software. - Childs, Hank; Geveci, Berk; Schroeder, Will; Meredith, Jeremy; Moreland, Kenneth; Sewell, Christopher; Kuhlen, Torsten; Bethel, E. Wes (Computer (00189162), 2013)
As the visualization research community reorients its software to address up-coming challenges, it must successfully deal with diverse processor architectures, distributed systems, various data sources, massive parallelism, multiple input and output devices, and interactivity.